Dolphin software accuracy in soft tissue facial profile prediction of Class II patients in orthognathic surgery - JODAS,Claudio Roberto Pacheco (2021)
ABSTRACT Objective: The present study aimed to analyze the accuracy of the Dolphin Imaging 11.9® computer program in the surgical prediction of the soft tissue facial profile. Methods: The investigators designed and implemented a retrospective study. It was used a sample of 55 patients, being 14 males and 41 females, aged from 19 to 55 years old. All patients were subjected to surgery orthognathic bimaxillary combined with mentoplasty, in Class II facial profile – Angle. Patients’ actual results were compared to the obtained up to a year and a half after the surgery procedure. The study was delineated in three phases. In the first phase, cephalometric preoperative radiographs were performed; in the second phase the postoperative cephalometries were made; in the third phase, the measurements of the soft profile of the virtual analysis were compared with the real post-surgical profile. The data was collected and subjected to statistical analysis in the “R” program, using the t test and ANOVA. Results: The results demonstrated that measures A’ and Eis were underestimated in -0.15 ± 0. 52 mm and -0.47 ± 1.05 mm, respectively, while measures Pg’ and ANL were overestimated at 0.76 ± 1.98 mm and 3.31 ± 3.60° respectively. There was no evidence of measures, Ls, Li and B’, being different between real and virtual. Conclusions: The results of this study suggest that Dolphin 11.9® computer program complies with the function of preserving with reliability virtual surgical planning.